Biliary peritonitis - Perdomo, Roberto (Cirugía del Uruguay, 2021)
The paper gives a definition of biliary peritonitis and 15 case histories are discussed. Their characteristics are grouped according to aspects of interest for the purpose of diagnosis. Paracentesis is of value in correct diagnosis.